(untitled) (Web of Teachers: Inderscience Research, 2025)
This article discusses language and culture in extensive terms and how they interact. Language serves as a cultural resource. Cultural diversity shapes the personality of the person who speaks the language. Language includes the layers of society or culture component if its structure, functions, and acquisition are taken into consideration. However, the cultural component does not consist of linguistically transmitted cultural information. It is a fundamental element of language that is present at all linguistic levels. A culture is the set of beliefs, values, customs, language, habits, and even material possessions that are passed down from one generation to the next. When people intend to learn a particular foreign language, they should be aware of that country’s culture.